2021
DOI: 10.1002/app.50440
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of epoxidized neem oil: A bio‐derived natural processing aid for elastomer

Abstract: Low cost and environment‐friendly bio‐oils are gaining market value as a plasticizer for elastomeric compounds. Unsaturated triglycerides of bio‐oils can be easily modified in various ways, like epoxidation, esterification, and so on. In the present work, 15 mole percentage of the total double bond content of the neem oil (NO) was epoxidized by acetic acid‐hydrogen peroxide system to synthesize epoxidized neem oil (ENO). NO and ENO were characterized by nuclear magnetic resonance spectroscopy, Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…Synthesized epoxidized oil was incorporated in the nitrile rubber matrix/styrene butadiene rubber matrix and compared with DOP vulcanizates. Overall, epoxidized neem oil is a comparable substitute for traditional vulcanizates; SEM results showed excellent carbon black dispersion and improvement in aging and thermal properties was observed 76 …”
Section: Epoxidation Of Bio‐based Raw Materialsmentioning
confidence: 94%
See 1 more Smart Citation
“…Synthesized epoxidized oil was incorporated in the nitrile rubber matrix/styrene butadiene rubber matrix and compared with DOP vulcanizates. Overall, epoxidized neem oil is a comparable substitute for traditional vulcanizates; SEM results showed excellent carbon black dispersion and improvement in aging and thermal properties was observed 76 …”
Section: Epoxidation Of Bio‐based Raw Materialsmentioning
confidence: 94%
“…Overall, epoxidized neem oil is a comparable substitute for traditional vulcanizates; SEM results showed excellent carbon black dispersion and improvement in aging and thermal properties was observed. 76 Similarly, neem oil is added as a plasticizer in the PLA matrix as a cost-effective alternative to other non-edible oils. Rajesh et al synthesized PLA and improved mechanical and thermal properties, including degradation, by incorporating neem oil into the polymer matrix.…”
Section: Epoxidation Of Neem Oilmentioning
confidence: 99%
“…However, it is crucial to conduct detailed studies on neem oil due to its toxicity, which can lead to contact allergies, lung irritation, and seizures, before considering its application in various uses. 80 Cardanol, extracted oil from cashew nut shells, has been modified through acrylation and epoxidation to produce cardanol-based acrylate. These modified compounds have demonstrated the ability to form polymers by incorporating the Darocur 1173 photoinitiator.…”
Section: Chemical Modification Of Vegetable Oils (Vos) Into 3d-printa...mentioning
confidence: 99%
“…In another investigation, neem oil was epoxidized and added as a plasticizer to rubbers, improving or maintaining comparable mechanical properties with respect to rubbers containing traditional plasticizers. The authors concluded that epoxidized neem oil may serve as a cheap and sustainable replacement for traditional petroleum-based rubber plasticizers [ 78 ]. Acrylates containing a triazine ring as a rigid core and long fatty acid chains as soft arms were synthesized and added to acrylated epoxidized soybean oil to produce UV-curable coatings with improved thermal and mechanical properties [ 79 ].…”
Section: Branched and Crosslinked Polymers Based On Pristine Or Chemically Modified Triglyceridesmentioning
confidence: 99%